RESULTS OF MULTICENTER STUDY OF PIDOTIMOD FOR THE PROPHYLAXIS OF ACUTE RESPIRATORY INFECTIONS IN FREQUENTLY AILING CHILDREN - L.S. Namazova-Baranova; S.M. Kharit; I.A. Tuzankina; T.N. Kozhevnikova; T.E. Taranushenko; A.A. Alekseeva (Вопросы современной педиатрии, 2010)
The article describes actual pediatric problem — frequent development of respiratory infections in children. Authors present the results of Russian multicenter study of effectiveness and safety of pidotimod (Imunorix) in frequently ailing children. It was shown that treatment with pidotimod during 30 days resulted in decreased rate of acute respiratory infections and their complications including ones with necessity of antibacterial therapy compared to children from control group. The dynamics of immunological rates in blood serum was studied. Key words: frequently ailing children, acute respiratory infections, prophylaxis, pidotimod. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(2):40-44)